Transcriptomics analysis for the identification of potential age-related genes and cells associated with three major urogenital cancers - Cao, Jinlong; Li, Jianpeng; Yang, Xin; Li, Pan; Yao, Zhiqiang; Han, Dali; Ying, Lijun; Wang, Lijie; Tian, Junqiang (Scientific reports, 2021)
Age is one of the most important risk factors of the occurrence for tumor patients. The majority of patients with urogenital cancers are the elderly, whose clinical characteristics are greatly affected by age and ageing. Our study aimed to explore age-related genes, cells, and biological changes in three common urogenital cancers via integrative bioinformatics analysis. First, mRNA (count format) and clinical data for bladder cancer, prostate cancer and renal cell carcinoma were downloaded from the Cancer Genome Atlas (TCGA). Through the comparison of clinicopathological characteristics, genes expression and cells infiltration between the old group and the young group, it was found that the clinical characteristics, genes and cells in the tumor microenvironment of different ages were quite different. And 4 key cells, 14 hub genes and some potential pathways were identified and considered as important factors. More importantly, we analyzed the differential landscape of the genes and cells from different perspectives, and confirmed its importance. In conclusion, we identified genes and cell types associated with age-related changes in the tumour microenvironment in urogenital cancer patients. These genes and cell types may play a critical role in the age-associated differences in clinicopathological characteristics among urogenital cancers, thus providing a link between ageing and cancer occurrence. The findings of this study may pave the way for the development of age-tailored approaches to treat cancer and other age-related diseases.